Le rire de la Chartreuse - Tomas, Ilda (Studia Romanica Posnaniensia, 2009)
To listen to Stendhal's laughter... The frequency of a verb denoting laughter and the analysis of what is constant and changeable in its use enable the reader to get into the spirit of the novel. The laughter radiates with the power of its sharpness, its attack and its passion to unmask; it gives the characters an ethical and egotistical dimension for it functions as a verbal germ of the conflict between an individual and the society and at the same time as the basic way to escape its real threats. Functioning as a beneficial upheaval, the sign of a political and social emancipation and discourse distancing itself, the laughter shows narcissistic predisposition of Stendhal’s character and his/her ontological loneliness. To listen to Stendhal's laughter - and to laugh with him - is to take part in the mediation characterized by irony, nobleness and clarity of vision, the mediation that the writer undertakes in difficult relations between the man and the world, the history, other people and himself.